A revision of Oriental Teloganodidae (Insecta, Ephemeroptera, Ephemerelloidea) - Sartori, Michel; Peters, Janice G.; Hubbard, Michael D. (Zootaxa, 2008)
Based on the examination of the type series of Cloe tristis Hagen, 1858 (type species of the genus Teloganodes Eaton, 1882) and material housed in several institutions, a revision of Oriental Teloganodidae is proposed. A lectotype is designated for Teloganodes tristis (Hagen, 1858) and the genus is redefined. The species T. major Eaton, 1884, is a subjective junior synonym of T. tristis Hagen, 1858 (syn. nov.). The genus Macafertiella Wang, 1996 is a subjective junior synonym of Teloganodes Eaton, 1882 (syn. nov.). A phylogenetic analysis is performed on all available nymphs. Teloganodes is restricted to Sri Lanka and the Western Ghats of India and encompasses the type species and T. dentatus Navás, 1931, T. insignis (Wang & McCafferty, 1996) (comb. nov.), and the following new species: T. tuberculatus sp. nov. (Sri Lanka), T. kodai sp. nov. (India), T. jacobusi sp. nov. (Sri Lanka) and T. hubbardi sp. nov. (Sri Lanka). The type material of T. dentata is redescribed. Species from Southeast Asia are assigned to two new genera. Dudgeodes gen. nov. includes the type species D. pescadori sp. nov. (Philippines) and D. lugens (Navás, 1933) comb. nov. (China), D. hutanis sp. nov. (Borneo), D. stephani sp. nov. (Borneo), D. ulmeri sp. nov. (Java, Sumatra), and D. celebensis sp. nov. (Sulawesi). The genus Derlethina gen. nov. is established for D. eloisae sp. nov. (Borneo). The egg morphology is presented for the first time for the family Teloganodidae. Affinities within the family and between related families are discussed and a key to distinguish all species known at the larval stage is proposed.